Keabsahan Bitcoin Sebagai Alat Pembayaran Global DalamPerspektifHukum PerdaganganInternasional - Ridanur Saputra Saputra (Universitas Muara Bungo, 2022)
Technological developments provide many conveniences for mankind, both conveniences related to work and daily activities to ease in trade matters. Bitcoin is part of a form of technological development, bitcoin is a digital currency (Cryptocurrency) circulating in cyberspace by using a blockchain system in transactions, with this system transactions with bitcoin are more systematic and secure. One of the advantages of bitcoin that is often considered is its low transaction costs, besides that data security is difficult to steal to privacy for those who need it, not only that the existence of bitcoin as a digital currency can also be used as a transaction tool or a tool used as a means of payment international trade. This study aims to find out whether the actual use of bitcoin as a transaction tool globally is permitted under national and international law, which then the author finds several obstacles in the application of bitcoin, one of which is the regulation related to the use of bitcoin as a digital currency that can be used as a tool of transaction. In Indonesia Bitcoin is regulated under Commodity Futures Supervisory Agency Regulation Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Crypto Asset Market (Crypto Assets) This regulation stipulates several provisions regarding the use of bitcoin in Indonesia where the principal in this regulation states that bitcoin is part of an asset. futures trading.Keywords : Bitcoin, cryptocurrency, International Trade